Low viscosity thickener for water-based wood coatings and preparation method thereof

A low-viscosity thickener for water-based wood coatings is developed using a combination of polylactic acid and polyethylene glycol block copolymers, modified through terminal amidation and sulfonation, to enhance hydrophilicity and form a dynamic cross-linking network that adjusts viscosity based on shear conditions, addressing the challenges of existing thickeners.

CN118978705BActive Publication Date: 2024-12-31ANHUI BONA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411474768.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-31
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Existing water-based paint thickeners for wood coatings are expensive, complex to produce, and require high concentrations to achieve desired rheological effects, which can affect the appearance and self-leveling properties of the coating.

Method used

A low-viscosity thickener is developed using a combination of polylactic acid and polyethylene glycol block copolymers, modified through terminal amidation and sulfonation, to enhance hydrophilicity and form a dynamic cross-linking network that adjusts viscosity based on shear conditions.

Benefits of technology

The modified polymers enhance the viscosity and stability of the coating, allowing for better fluidity and leveling, reducing the gloss and aesthetics of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978705B_ABST
    Figure CN118978705B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of coating thickeners, and provides a low-viscosity thickener for water-based wood coatings and a preparation method thereof. Although the water-based coating thickeners on the market can increase the viscosity of the coating, they may affect the transparency and self-leveling properties of the coating. In addition, in order to achieve the desired rheological effect, the thickener may need to be used at a higher concentration, thereby increasing the cost and affecting the appearance of the coating. The thickener of the present invention is a thickener synthesized by polylactic acid and polyethylene glycol block copolymers, in which polylactic acid provides a hydrophobic skeleton and polyethylene glycol provides hydrophilicity. The polylactic acid segments are further modified by terminal amidation and multi-point cross-linked sulfonated polyethylene glycol to form a stable three-dimensional network structure, thereby improving the viscosity and leveling properties of the coating and improving the anti-sagging property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating thickeners and relates to a low-viscosity thickener for water-based wood coatings and a preparation method thereof. Background Art

[0002] Water-based paint is widely used in various types of buildings, furniture, automobiles and industrial coatings. It is favored for its low volatile organic compound emissions, environmental protection, safety and other advantages. The water-based paint thickeners on the market mainly include fine powder inorganic substances and synthetic polymers, such as hydroxyethyl cellulose or acrylic acid derivatives. The Chinese patent with the authorization announcement number CN106957557B discloses an associative thickener for water-based UV polyurethane coatings and a preparation method thereof. The thickener of water-based paint is prepared by using polyethylene glycol, diisocyanate, enol capping agent, dibutyltin dilaurate and isocyanate. However, the steps of heating vacuum dehydration designed in the preparation process increase the complexity of processing and increase production costs. The Chinese patent with the publication number CN104789029A discloses a thickener for thickening water-based paint, which uses sodium bentonite after burning to react with sulfuric acid solution for acidification, and washes, grinds and sieves. The sodium bentonite after burning designed in the preparation process is large in amount and has poor suspension and thickening properties, which cannot meet the requirements of wood coatings. Although these thickeners can increase the viscosity of the coating, they are expensive, complicated to work on, and may affect the self-leveling properties of the coating. In addition, in order to achieve the desired rheological effect, these thickeners may require a higher concentration, which increases the cost and affects the appearance of the coating. Therefore, the development of low-concentration but high-thickening efficiency thickeners has become the key to solving the problem. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a low-viscosity thickener for water-based wood coatings and a preparation method thereof, which is achieved through the design and modification of polylactic acid and polyethylene glycol block copolymers. Polylactic acid provides the necessary hydrophobic skeleton, polyethylene glycol provides the hydrophilic segment, and the terminal amidation modification improves the anti-sagging property of the coating system, thereby meeting the needs of actual production.

[0004] To achieve this object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing a low viscosity thickener for waterborne wood coatings, the preparation method comprising:

[0006] Step S1, dissolving polylactic acid in a reaction solvent, stirring at a first stirring speed to fully dissolve the polylactic acid, adding an amination reagent and a first catalyst under the protection of an inert gas, then heating to a first temperature for full reaction, after the reaction, adding the cooled polymer solution to a cold ethanol solution, and stirring the solution at a second stirring speed to ensure that the polymer in the solution is uniformly dispersed and precipitated, collecting the precipitate after standing, washing it with cold ethanol, and removing the residual ethanol with a rotary evaporator to obtain an amination polylactic acid;

[0007] Step S2, dissolving the amino polylactic acid in a reaction solvent, adding an amidation agent and a second catalyst, heating to a second temperature under the protection of an inert gas, and fully reacting at a third stirring speed, washing the precipitated product with cold ethanol after the reaction is completed, and removing the residual ethanol by a rotary evaporator to obtain terminal amide polylactic acid;

[0008] Step S3, dissolving polyethylene glycol in a dry reaction solvent, stirring at a fourth stirring speed to fully dissolve the polyethylene glycol, adding a sulfonating agent and a third catalyst under the protection of an inert gas, and maintaining the reaction temperature at the third temperature, heating to a fourth temperature after the addition is completed to fully react, removing the solvent by a rotary evaporator, and precipitating and purifying in cold ethanol to obtain sulfonated polyethylene glycol;

[0009] Step S4, dissolving the sulfonated polyethylene glycol in a reaction solvent, adding a cross-linking agent, stirring at a fifth stirring speed under the protection of an inert gas, reacting sufficiently at a fifth temperature, removing the solvent by a rotary evaporator, precipitating with cold ethanol and washing for multiple times, to obtain a multi-point cross-linked sulfonated polyethylene glycol;

[0010] Step S5, dissolving the terminal amide polylactic acid and the multi-point cross-linked sulfonated polyethylene glycol in a reaction solvent, adding a fourth catalyst, fully reacting at a sixth temperature, performing ring-opening polymerization, and adding an antioxidant and an ultraviolet absorber. After the reaction is completed, removing the solvent by a rotary evaporator, using cold ethanol for precipitation and washing, to obtain a low-viscosity thickener for water-based wood coatings.

[0011] Waterborne paints are widely used in various types of architectural, furniture, automotive and industrial coatings. They are highly favored for their low volatile organic compound emissions, environmental protection, safety and other advantages. In the formulation of waterborne paints, thickeners are a key additive used to adjust the rheological properties of the paint so that it exhibits appropriate fluidity and viscosity under different shear conditions. The main functions of waterborne paint thickeners include: (1) increasing the viscosity of the paint. By adding thickeners, the paint exhibits a higher viscosity under static conditions to prevent the stratification and precipitation of the paint during storage; (2) thickeners can adjust the brushing, rolling or spraying performance of the paint during construction to avoid sagging while ensuring the uniformity of the coating; (3) thickeners can give the paint shear thinning properties, that is, it exhibits a lower viscosity under high shear (such as spraying, brushing) to facilitate construction, and restores a higher viscosity under low shear or static conditions to maintain the thickness of the coating and prevent sagging.

[0012] Currently, the common types of thickeners for water-based paints are: (1) Cellulose thickeners, such as hydroxyethyl cellulose and carboxymethyl cellulose, have high water solubility and thickening ability, but poor water resistance; (2) Synthetic polymer thickeners, such as polyacrylic acid and polyurethane, increase the viscosity of the paint by physical cross-linking or chemical reaction of the molecular chains, and are often used in water-based paints with high requirements for rheological properties; (3) Inorganic thickeners, such as bentonite and silica, increase the viscosity by increasing the physical interaction between particles, but their rheological properties can be adjusted more limitedly.

[0013] Although existing thickener technology can already meet certain coating performance requirements, it still faces some technical bottlenecks and challenges in practical applications: (1) Problems caused by high concentration use. The addition of high concentration thickeners will have an adverse effect on the gloss of the coating. After the coating film dries, the surface may become less smooth, thereby reducing the gloss and aesthetics of the coating film, especially in coating applications with high surface gloss requirements (such as furniture and automotive coatings); (2) Although high-viscosity coatings can prevent sagging, they may affect the self-leveling properties of the coating, resulting in the coating film being not smooth enough after construction, and problems such as brush marks and roller marks.

[0014] The role of terminal amidation of polylactic acid is:

[0015] (1) Improve the polarity and hydrogen bonding of the polylactic acid chain. Through terminal amidation, a highly polar amide group is introduced to the end of the polylactic acid chain. The enhanced polarity helps it to form hydrogen bonds with molecules in the aqueous phase (such as water, resin or other hydrophilic substances), thereby improving the dispersibility of polylactic acid in water-based coatings. The hydrogen bond donor and acceptor properties of the amide group enable it to interact with water molecules or other polar substances, promoting the dissolution and stability of the polylactic acid block in the aqueous phase, thereby improving the overall efficiency of the thickener;

[0016] (2) The amidated polylactic acid ends have stronger interaction forces, which help the polylactic acid segments to form stable self-assembled structures in aqueous media through intermolecular forces (such as hydrogen bonds and van der Waals forces), thereby enhancing the effect of the thickener. The introduction of amide groups improves the hydrophilicity of the polylactic acid segments. At the same time, their amphiphilic properties enable the terminal amide groups to exhibit better self-assembly behavior in aqueous systems, helping to form structures such as nanomicelles and colloids that help to increase the viscosity of the system.

[0017] (3) The modification of terminal amidated polylactic acid helps to regulate the dynamic network between molecules, so that the coating can exhibit good shear thinning properties when subjected to shear force, thereby improving the fluidity and leveling of the coating. The amide group can temporarily break the weak interactions between its molecules under the action of shear force, and the fluidity of the coating is improved. When the shear force decreases or disappears, the amide group quickly re-forms physical cross-linking through hydrogen bonding and other effects, and the thickening effect of the coating is restored.

[0018] The effects of sulfonation and multi-point cross-linking of polyethylene glycol are:

[0019] (1) Sulfonated polyethylene glycol introduces sulfonic acid groups into the polymer chain, making it more polar and ionic, so that it can form strong interactions with the water phase and other polar molecules. Multi-point cross-linking makes the thickening effect of polyethylene glycol more significant, and it can provide sufficient viscosity even at low concentrations. The sulfonic acid group is a strong polar group that can form strong hydrogen bonds and charge interactions with water molecules, which enhances the solubility and extensibility of polyethylene glycol in water-based coating systems, making it easier to form an intermolecular cross-linking network and increase the viscosity of the system. At the same time, the multi-point cross-linking structure of sulfonated polyethylene glycol means that there may be multiple sulfonic acid groups on each polyethylene glycol molecule, which can interact with multiple water molecules or other coating components at the same time to form a three-dimensional network;

[0020] (2) Multi-point cross-linked sulfonated polyethylene glycol can enhance the thixotropy and shear thinning properties of the coating through its flexible molecular chain structure and multi-point cross-linking characteristics. In this way, under high shear conditions (such as brushing and spraying), the viscosity of the coating decreases and it is easy to flow. Under low shear or when stationary, the viscosity recovers rapidly to prevent sagging. The multi-point cross-linked network formed by the sulfonic acid groups and other polar molecules in the coating (such as water molecules and resins) can be partially broken when subjected to high shear force, making the coating exhibit a lower viscosity. This dynamic network helps the fluidity and leveling of the coating during construction. When the shear force decreases or disappears, the cross-linked network recovers rapidly, the viscosity rises, and the coating is prevented from sagging.

[0021] The modified polylactic acid and the modified sulfonated polyethylene glycol have multiple interactions, which make them show strong synergistic thickening effect in water-based coatings, specifically:

[0022] (1) The sulfonic acid groups and amino groups form stable physical crosslinks through electrostatic interactions. This mutual attraction between charges helps to build a microscopic network structure in the aqueous system, thereby enhancing the thickening effect of the polymer. Sulfonated polyethylene glycol dissociates into negatively charged sulfonate ions in water, while the amino groups on the aminated polylactic acid carry positive charges. The interaction between these positive and negative charges produces dynamic crosslinking points, thereby improving the mechanical strength and viscosity of the entire coating system.

[0023] (2) The amide group can form hydrogen bonds with the sulfonic acid group and the amino group. The presence of hydrogen bonds further stabilizes the weak interactions between the polymer chains, allowing the two modified polymers to form a tighter physical cross-linking network in the water-based coating. Although the strength of hydrogen bonds is lower than that of electrostatic interactions, they can provide additional intermolecular attraction in water, helping to enhance the overall viscosity of the coating.

[0024] As a preferred technical solution of the present invention, in step S1, the amount of the polylactic acid substance is 5-10mmol, for example, it can be 5.0mmol, 5.5mmol, 6.0mmol, 6.5mmol, 7.0mmol, 7.5mmol, 8.0mmol, 8.5mmol, 9.0mmol, 9.5mmol or 10.0mmol, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional examples, the volume of the reaction solvent is 200-250 mL, for example, it can be 200 mL, 205 mL, 210 mL, 215 mL, 220 mL, 225 mL, 230 mL, 235 mL, 240 mL, 245 mL or 250 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional examples, the first stirring speed is 300-400rpm, for example, it can be 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm or 400rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the stirring time of the first stirring speed is 30-50 min, for example, it can be 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min or 50 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional instances, the ventilation rate is 5-7 mL / min, for example, it can be 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min, 5.8 mL / min, 6.0 mL / min, 6.2 mL / min, 6.4 mL / min, 6.6 mL / min, 6.8 mL / min or 7.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional examples, the volume of the amination reagent is 3-5 mL, for example, it can be 3.0 mL, 3.2 mL, 3.4 mL, 3.6 mL, 3.8 mL, 4.0 mL, 4.2 mL, 4.4 mL, 4.6 mL, 4.8 mL or 5.0 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the mass of the first catalyst is 0.2-0.5g, for example, it can be 0.20g, 0.23g, 0.26g, 0.29g, 0.32g, 0.35g, 0.38g, 0.41g, 0.44g, 0.47g or 0.50g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional instances, the first temperature is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional examples, the reaction time at the first temperature is 4-6h, for example, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the temperature of the cold ethanol is 0-8°C, for example, it can be 0.0°C, 0.8°C, 1.6°C, 2.4°C, 3.2°C, 4.0°C, 4.8°C, 5.6°C, 6.4°C, 7.2°C or 8.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional examples, the second stirring speed is 200-300 rpm, for example, it can be 200 rpm, 210 rpm, 220 rpm, 330 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the stirring time of the second stirring speed is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the standing time is 10-20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] As a preferred technical solution of the present invention, in step S2, the amount of the amino polylactic acid is 2-5 mmol, for example, it can be 2.0 mmol, 2.3 mmol, 2.6 mmol, 2.9 mmol, 3.2 mmol, 3.5 mmol, 3.8 mmol, 4.1 mmol, 4.4 mmol, 4.7 mmol or 5.0 mmol, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional examples, the volume of the reaction solvent is 200-250 mL, for example, it can be 200 mL, 205 mL, 210 mL, 215 mL, 220 mL, 225 mL, 230 mL, 235 mL, 240 mL, 245 mL or 250 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional examples, the amount of the amidation reagent is 2-5 mmol, for example, 2.0 mmol, 2.3 mmol, 2.6 mmol, 2.9 mmol, 3.2 mmol, 3.5 mmol, 3.8 mmol, 4.1 mmol, 4.4 mmol, 4.7 mmol or 5.0 mmol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the mass of the second catalyst is 1-2g, for example, it can be 1.0g, 1.1g, 1.2g, 1.3g, 1.4g, 1.5g, 1.6g, 1.7g, 1.8g, 1.9g or 2.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional instances, the ventilation rate is 5-7 mL / min, for example, it can be 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min, 5.8 mL / min, 6.0 mL / min, 6.2 mL / min, 6.4 mL / min, 6.6 mL / min, 6.8 mL / min or 7.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional instances, the second temperature is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional examples, the third stirring speed is 350-450rpm, for example, it can be 350rpm, 360rpm, 370rpm, 380rpm, 390rpm, 400rpm, 410rpm, 420rpm, 430rpm, 440rpm or 450rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional examples, the reaction time at the second temperature is 3-5h, for example, 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] As a preferred technical solution of the present invention, in step S3, the amount of the polyethylene glycol substance is 5-10 mmol, for example, it can be 5.0 mmol, 5.5 mmol, 6.0 mmol, 6.5 mmol, 7.0 mmol, 7.5 mmol, 8.0 mmol, 8.5 mmol, 9.0 mmol, 9.5 mmol or 10.0 mmol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional examples, the fourth stirring speed is 400-500rpm, for example, it can be 400rpm, 410rpm, 420rpm, 430rpm, 440rpm, 450rpm, 460rpm, 470rpm, 480rpm, 490rpm or 500rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the stirring time of the fourth stirring speed is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional instances, the ventilation rate is 5-7 mL / min, for example, it can be 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min, 5.8 mL / min, 6.0 mL / min, 6.2 mL / min, 6.4 mL / min, 6.6 mL / min, 6.8 mL / min or 7.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional examples, the amount of the sulfonic acid reagent is 6-11 mmol, for example, 6.0 mmol, 6.5 mmol, 7.0 mmol, 7.5 mmol, 8.0 mmol, 8.5 mmol, 9.0 mmol, 9.5 mmol, 10.0 mmol, 10.5 mmol or 11.0 mmol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the volume of the third catalyst is 2-3 mL, for example, it can be 2.0 mL, 2.1 mL, 2.2 mL, 2.3 mL, 2.4 mL, 2.5 mL, 2.6 mL, 2.7 mL, 2.8 mL, 2.9 mL or 3.0 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional instances, the third temperature is 0-5°C, for example, it can be 0.0°C, 0.5°C, 1.0°C, 1.5°C, 2.0°C, 2.5°C, 3.0°C, 3.5°C, 4.0°C, 4.5°C or 5.0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional instances, the fourth temperature is 30-40°C, for example, it can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional examples, the reaction time at the fourth temperature is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] As a preferred technical solution of the present invention, in step S4, the amount of the sulfonated polyethylene glycol is 2-5 mmol, for example, 2.0 mmol, 2.3 mmol, 2.6 mmol, 2.9 mmol, 3.2 mmol, 3.5 mmol, 3.8 mmol, 4.1 mmol, 4.4 mmol, 4.7 mmol or 5.0 mmol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional examples, the volume of the reaction solvent is 200-250 mL, for example, it can be 200 mL, 205 mL, 210 mL, 215 mL, 220 mL, 225 mL, 230 mL, 235 mL, 240 mL, 245 mL or 250 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In some optional examples, the amount of the cross-linking agent is 2.1-5.1 mmol, for example, 2.1 mmol, 2.4 mmol, 2.7 mmol, 3.0 mmol, 3.3 mmol, 3.6 mmol, 3.9 mmol, 4.2 mmol, 4.5 mmol, 4.8 mmol or 5.1 mmol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional instances, the ventilation rate is 5-7 mL / min, for example, it can be 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min, 5.8 mL / min, 6.0 mL / min, 6.2 mL / min, 6.4 mL / min, 6.6 mL / min, 6.8 mL / min or 7.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional examples, the fifth stirring speed is 250-350rpm, for example, it can be 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm, 310rpm, 320rpm, 330rpm, 340rpm or 350rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional instances, the fifth temperature is 35-45°C, for example, it can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In some optional examples, the reaction time at the fifth temperature is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] As a preferred technical solution of the present invention, in step S5, the amount of the terminal amide polylactic acid is 2-4mmol, for example, it can be 2.0mmol, 2.2mmol, 2.4mmol, 2.6mmol, 2.8mmol, 3.0mmol, 3.2mmol, 3.4mmol, 3.6mmol, 3.8mmol or 4.0mmol, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional examples, the volume of the reaction solvent is 200-250 mL, for example, it can be 200 mL, 205 mL, 210 mL, 215 mL, 220 mL, 225 mL, 230 mL, 235 mL, 240 mL, 245 mL or 250 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional examples, the mass of the fourth catalyst is 0.2-0.5g, for example, it can be 0.20g, 0.23g, 0.26g, 0.29g, 0.32g, 0.35g, 0.38g, 0.41g, 0.44g, 0.47g, 0.50g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In some optional instances, the sixth temperature is 110-130°C, for example, it can be 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional examples, the reaction time at the sixth temperature is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some optional examples, the mass of the antioxidant is 1-2g, for example, it can be 1.0g, 1.1g, 1.2g, 1.3g, 1.4g, 1.5g, 1.6g, 1.7g, 1.8g, 1.9g or 2.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In some optional examples, the mass of the ultraviolet absorber is 1-2g, for example, it can be 1.0g, 1.1g, 1.2g, 1.3g, 1.4g, 1.5g, 1.6g, 1.7g, 1.8g, 1.9g or 2.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In a second aspect, the present invention provides a low viscosity thickener for waterborne wood coatings.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] (1) The unique molecular structure of block copolymers is composed of different hydrophilic and hydrophobic segments. The hydrophilic block polyethylene glycol interacts strongly with water molecules, while the hydrophobic block polylactic acid forms a physical cross-linked network with other organic components in the coating through hydrophobic association. The block structure generates multiple association points through interaction, which enhances the entanglement and physical cross-linking between molecular chains, thereby effectively increasing the viscosity of the system at a lower concentration. The multi-point association and network structure can more effectively hinder molecular movement than linear polymers, showing a more efficient thickening effect;

[0071] (2) Block copolymer thickeners can significantly improve the stability of waterborne coating systems and prevent the sedimentation of pigment particles or other solid components in the coating. The hydrophilic blocks in the block copolymers have a strong interaction with the water phase and can effectively encapsulate and disperse the solid components in the coating to form a stable colloid or suspension system. At the same time, the physical cross-linking network of the hydrophobic blocks can further increase the viscoelasticity of the system and enhance the support for the particles.

[0072] (3) The molecular design of block copolymers introduces different functional fragments, making their thickening effect higher than that of traditional thickeners. Since block copolymers can spontaneously form a stable cross-linked network at lower concentrations, the amount of thickener in the coating system is reduced. The biodegradability and environmental friendliness of block copolymers meet the requirements of environmentally friendly coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 A flow chart of a method for preparing a low-viscosity thickener for water-based wood coatings provided in Examples 1-8 of the present invention;

[0074] Figure 2 The Fourier transform infrared spectra of polylactic acid, polyethylene glycol and polylactic acid-polyethylene glycol in Example 1 of the present invention are shown;

[0075] Figure 3 The XRD diffraction patterns of polylactic acid, polyethylene glycol and polylactic acid-polyethylene glycol in Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0076] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0077] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications and manufacturer information are as follows:

[0078] Polylactic acid, content ≥98%, Beijing Thompson Biotechnology Co., Ltd.;

[0079] Dichloromethane, content ≥99%, Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0080] Nitrogen, content ≥99%, Tianjin Fuyu Fine Chemical Co., Ltd.;

[0081] Ethylenediamine monohydrate, content ≥98%, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0082] Isophorone diisocyanate, content ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0083] Ethanol, purity ≥99%, Henan Zhongbin Chemical Technology Co., Ltd.;

[0084] N-hydroxysuccinimide, purity ≥99%, Shanghai Changming Pharmaceutical Technology Co., Ltd.;

[0085] N,N'-dicyclohexylcarbodiimide, purity ≥98%, Hubei Tianrun Pharmaceutical Chemical Co., Ltd.;

[0086] Polyethylene glycol, purity ≥98%, Shandong Leli New Materials Co., Ltd.;

[0087] Sulfonyl chloride, purity ≥98%, Shandong Century Chaoyue Chemical Co., Ltd.;

[0088] Triethylamine, purity ≥99%, Shandong Ruishuang Chemical Co., Ltd.;

[0089] Triethylenetetramine, purity ≥98%, Xiamen Geruida Chemical Co., Ltd.;

[0090] Stannous octoate, purity ≥95%, Hubei Xinmingtai Chemical Co., Ltd.;

[0091] 2,6-di-tert-butyl-4-methylphenol, purity ≥99%, Hubei Nordina Biotechnology Co., Ltd.;

[0092] 2-(2'-Hydroxy-5'-octylphenyl)benzotriazole, purity ≥98%, Hubei Nordina Biotechnology Co., Ltd.;

[0093] Other raw materials can be purchased from the market.

[0094] Example 1

[0095] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1As shown, the preparation method specifically comprises the following steps:

[0096] Step S1, dissolving 5.2 mmol of polylactic acid in 220 mL of dichloromethane, stirring at 330 rpm for 36 min to fully dissolve the polylactic acid, adding 3.6 mL of ethylenediamine monohydrate and 0.26 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 5.5 mL / min, then heating to 47°C for full reaction for 4.8 h, after the reaction is completed, adding the cooled polymer solution to a 5°C cold ethanol solution, and stirring the solution at 220 rpm for 26 min to ensure that the polymer in the solution is evenly dispersed and precipitated, collecting the precipitate after standing for 15 min, washing it with cold ethanol, and removing the residual ethanol with a rotary evaporator to obtain amino polylactic acid;

[0097] Step S2, dissolving the 2.5 mmol of the amino polylactic acid in 210 mL of dichloromethane, adding 2.6 mmol of N-hydroxysuccinimide and 1.2 g of N,N'-dicyclohexylcarbodiimide, heating to 43°C under nitrogen protection at a ventilation rate of 5.5 mL / min, and fully reacting at a speed of 380 rpm for 3.8 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0098] Step S3, dissolving 6.2 mmol polyethylene glycol in 210 mL dry dichloromethane, stirring at 420 rpm for 26 min to fully dissolve the polyethylene glycol, adding 6.3 mmol sulfonyl chloride and 2.4 mL triethylamine under nitrogen protection at a ventilation rate of 5.5 mL / min, and maintaining the reaction temperature at 2.5° C. After the addition is completed, the temperature is raised to 31° C. to fully react for 4.8 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0099] Step S4, dissolving the 2.7 mmol sulfonated polyethylene glycol in 210 mL dichloromethane, adding 2.8 mmol triethylenetetramine, stirring at 320 rpm under nitrogen protection with a ventilation rate of 5.5 mL / min, reacting at 39° C. for 4.9 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0100] Step S5, dissolving 2.1 mmol of terminal amide polylactic acid and 6.3 mmol of multi-point cross-linked sulfonated polyethylene glycol in 220 mL of dichloromethane, adding 0.34 g of stannous octoate, fully reacting at 127° C. for 4.7 hours, performing ring-opening polymerization, and adding 1.3 g of 2,6-di-tert-butyl-4-methylphenol and 1.6 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0101] Figure 2 The infrared images of polylactic acid, polyethylene glycol and polylactic acid-polyethylene glycol are shown in Figure 2990 cm -1 The characteristic peak of CH stretching vibration of polylactic acid is 1750cm -1 The characteristic peak of C=O bending vibration of polylactic acid is 1125cm -1 The peak at 2880cm is the characteristic peak of CO stretching vibration of polylactic acid; -1 The characteristic peak of CH stretching vibration of polyethylene glycol is 1280 cm -1 The peak at is the characteristic peak of C=O bending vibration of polyethylene glycol. Figure 3 These are the XRD diagrams of polylactic acid, polyethylene glycol and polylactic acid-polyethylene glycol. Polylactic acid exhibits a broader diffraction peak, indicating that it has fewer crystallinity peaks. The composite sample has characteristic peaks of polylactic acid and polyethylene glycol, indicating that the thickener was successfully prepared.

[0102] Example 2

[0103] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0104] Step S1, dissolving 6.1 mmol of polylactic acid in 240 mL of dichloromethane, stirring at 310 rpm for 43 min to fully dissolve the polylactic acid, adding 3.2 mL of ethylenediamine monohydrate and 0.23 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 6.4 mL / min, then heating to 53° C. to fully react for 5.1 h. After the reaction is completed, the cooled polymer solution is added to a 4.2° C. cold ethanol solution, and the solution is stirred at 250 rpm for 22 min to ensure that the polymer in the solution is evenly dispersed and precipitated. After standing for 12 min, the precipitate is collected and washed with cold ethanol, and the residual ethanol is removed using a rotary evaporator to obtain amino polylactic acid;

[0105] Step S2, dissolving the 2.9 mmol of the amino polylactic acid in 230 mL of dichloromethane, adding 3.0 mmol of N-hydroxysuccinimide and 1.2 g of N,N'-dicyclohexylcarbodiimide, heating to 41°C under nitrogen protection at a ventilation rate of 6.4 mL / min, and fully reacting at a speed of 410 rpm for 4.2 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0106] Step S3, dissolving 6.7 mmol polyethylene glycol in 230 mL dry dichloromethane, stirring at 470 rpm for 22 min to fully dissolve the polyethylene glycol, adding 7.8 mmol sulfonyl chloride and 2.2 mL triethylamine under nitrogen protection at a ventilation rate of 6.4 mL / min, and maintaining the reaction temperature at 3.1° C. After the addition is completed, the temperature is raised to 35° C. to fully react for 5.1 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0107] Step S4, dissolving the 3.2 mmol sulfonated polyethylene glycol in 205 mL dichloromethane, adding 3.3 mmol triethylenetetramine, stirring at 290 rpm under nitrogen protection with a ventilation rate of 6.4 mL / min, reacting at 42° C. for 5.2 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0108] Step S5, dissolving 2.6 mmol of terminal amide polylactic acid and 7.8 mmol of multi-point cross-linked sulfonated polyethylene glycol in 235 mL of dichloromethane, adding 0.27 g of stannous octoate, fully reacting at 116° C. for 5.1 h, performing ring-opening polymerization, and adding 1.1 g of 2,6-di-tert-butyl-4-methylphenol and 1.4 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0109] Example 3

[0110] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0111] Step S1, dissolving 5.8 mmol of polylactic acid in 215 mL of dichloromethane, stirring at 370 rpm for 39 min to fully dissolve the polylactic acid, adding 4.0 mL of ethylenediamine monohydrate and 0.33 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 5.2 mL / min, then heating to 48°C for full reaction for 5.6 h, after the reaction is completed, adding the cooled polymer solution to a 6.4°C cold ethanol solution, and stirring the solution at 220 rpm for 27 min to ensure that the polymer in the solution is evenly dispersed and precipitated, collecting the precipitate after standing for 16 min, washing it with cold ethanol, and removing the residual ethanol with a rotary evaporator to obtain amino polylactic acid;

[0112] Step S2, dissolving the 3.3 mmol of the amino polylactic acid in 225 mL of dichloromethane, adding 3.4 mmol of N-hydroxysuccinimide and 1.5 g of N,N'-dicyclohexylcarbodiimide, heating to 46°C under nitrogen protection at a ventilation rate of 5.2 mL / min, and fully reacting at a speed of 370 rpm for 3.8 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0113] Step S3, dissolving 7.2 mmol of polyethylene glycol in 245 mL of dry dichloromethane, stirring at 430 rpm for 25 min to fully dissolve the polyethylene glycol, adding 8.3 mmol of sulfonyl chloride and 2.6 mL of triethylamine under nitrogen protection at a ventilation rate of 5.2 mL / min, and maintaining the reaction temperature at 2.6° C. After the addition is completed, the temperature is raised to 30° C. to fully react for 5.8 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0114] Step S4, dissolving the 2.6 mmol sulfonated polyethylene glycol in 225 mL dichloromethane, adding 2.7 mmol triethylenetetramine, stirring at 330 rpm under nitrogen protection with a ventilation rate of 5.2 mL / min, reacting at 40° C. for 5.4 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0115] Step S5, dissolving 2.3 mmol of terminal amide polylactic acid and 6.9 mmol of multi-point cross-linked sulfonated polyethylene glycol in 210 mL of dichloromethane, adding 0.35 g of stannous octoate, fully reacting at 123° C. for 5.4 h, performing ring-opening polymerization, and adding 1.5 g of 2,6-di-tert-butyl-4-methylphenol and 1.2 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0116] Example 4

[0117] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0118] Step S1, dissolving 5.5 mmol of polylactic acid in 210 mL of dichloromethane, stirring at 310 rpm for 44 min to fully dissolve the polylactic acid, adding 4.3 mL of ethylenediamine monohydrate and 0.45 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 6.4 mL / min, then heating to 54° C. to fully react for 4.6 h. After the reaction is completed, the cooled polymer solution is added to a 3.9° C. cold ethanol solution, and the solution is stirred at 270 rpm for 21 min to ensure that the polymer in the solution is evenly dispersed and precipitated. After standing for 13 min, the precipitate is collected and washed with cold ethanol, and the residual ethanol is removed using a rotary evaporator to obtain amino polylactic acid;

[0119] Step S2, dissolving 4.2 mmol of the amino polylactic acid in 240 mL of dichloromethane, adding 4.3 mmol of N-hydroxysuccinimide and 1.6 g of N,N'-dicyclohexylcarbodiimide, heating to 42° C. under nitrogen protection at a ventilation rate of 6.4 mL / min, and fully reacting at a speed of 410 rpm for 4.3 h. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0120] Step S3, dissolving 6.3 mmol polyethylene glycol in 225 mL dry dichloromethane, stirring at 460 rpm for 21 min to fully dissolve the polyethylene glycol, adding 7.8 mmol sulfonyl chloride and 2.3 mL triethylamine under nitrogen protection at a ventilation rate of 6.4 mL / min, and maintaining the reaction temperature at 3.0° C. After the addition is completed, the temperature is raised to 33° C. to fully react for 5.1 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0121] Step S4, dissolving the 3.6 mmol sulfonated polyethylene glycol in 210 mL dichloromethane, adding 3.7 mmol triethylenetetramine, stirring at 300 rpm under nitrogen protection with a ventilation rate of 6.4 mL / min, reacting at 37° C. for 4.8 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0122] Step S5, dissolving 3.1 mmol of terminal amide polylactic acid and 9.3 mmol of multi-point cross-linked sulfonated polyethylene glycol in 250 mL of dichloromethane, adding 0.47 g of stannous octoate, fully reacting at 128° C. for 4.5 hours, performing ring-opening polymerization, and adding 1.7 g of 2,6-di-tert-butyl-4-methylphenol and 1.5 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0123] Example 5

[0124] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0125] Step S1, dissolving 7.1 mmol of polylactic acid in 230 mL of dichloromethane, stirring at 380 rpm for 36 min to fully dissolve the polylactic acid, adding 3.9 mL of ethylenediamine monohydrate and 0.29 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 5.7 mL / min, then heating to 47°C for full reaction for 5.5 h, after the reaction is completed, adding the cooled polymer solution to a 7.0°C cold ethanol solution, and stirring the solution at 260 rpm for 25 min to ensure that the polymer in the solution is evenly dispersed and precipitated, collecting the precipitate after standing for 16 min, washing it with cold ethanol, and removing the residual ethanol with a rotary evaporator to obtain amino polylactic acid;

[0126] Step S2, dissolving the 2.2 mmol of the amino polylactic acid in 210 mL of dichloromethane, adding 2.3 mmol of N-hydroxysuccinimide and 1.1 g of N,N'-dicyclohexylcarbodiimide, heating to 44°C under nitrogen protection at a ventilation rate of 5.7 mL / min, and fully reacting at a speed of 380 rpm for 3.6 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0127] Step S3, dissolving 5.6 mmol polyethylene glycol in 205 mL dry dichloromethane, stirring at 410 rpm for 28 min to fully dissolve the polyethylene glycol, adding 6.8 mmol sulfonyl chloride and 2.0 mL triethylamine under nitrogen protection at a ventilation rate of 5.7 mL / min, and maintaining the reaction temperature at 1.5° C. After the addition is completed, the temperature is raised to 37° C. to fully react for 4.4 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0128] Step S4, dissolving the 2.8 mmol sulfonated polyethylene glycol in 225 mL dichloromethane, adding 3.0 mmol triethylenetetramine, stirring at 330 rpm under nitrogen protection with a ventilation rate of 5.7 mL / min, reacting at 42° C. for 5.3 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0129] Step S5, dissolving 2.5 mmol of terminal amide polylactic acid and 7.5 mmol of multi-point cross-linked sulfonated polyethylene glycol in 230 mL of dichloromethane, adding 0.36 g of stannous octoate, fully reacting at 117° C. for 5.6 hours, performing ring-opening polymerization, and adding 1.1 g of 2,6-di-tert-butyl-4-methylphenol and 1.4 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0130] Example 6

[0131] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0132] Step S1, dissolving 8.6 mmol of polylactic acid in 240 mL of dichloromethane, stirring at 340 rpm for 47 min to fully dissolve the polylactic acid, adding 3.72 mL of ethylenediamine monohydrate and 0.33 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 6.3 mL / min, then heating to 54° C. to fully react for 4.1 h, after the reaction is completed, adding the cooled polymer solution to a 5.5° C. cold ethanol solution, and stirring the solution at 230 rpm for 27 min to ensure that the polymer in the solution is evenly dispersed and precipitated, collecting the precipitate after standing for 12 min, washing it with cold ethanol, and removing the residual ethanol with a rotary evaporator to obtain amino polylactic acid;

[0133] Step S2, dissolving the 3.1 mmol of the amino polylactic acid in 220 mL of dichloromethane, adding 3.2 mmol of N-hydroxysuccinimide and 1.6 g of N,N'-dicyclohexylcarbodiimide, heating to 46°C under nitrogen protection at a ventilation rate of 6.3 mL / min, and fully reacting at a speed of 430 rpm for 4.2 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0134] Step S3, dissolving 7.4 mmol polyethylene glycol in 240 mL dry dichloromethane, stirring at 470 rpm for 22 min to fully dissolve the polyethylene glycol, adding 8.5 mmol sulfonyl chloride and 2.6 mL triethylamine under nitrogen protection at a ventilation rate of 6.3 mL / min, and maintaining the reaction temperature at 3.5° C. After the addition is completed, the temperature is raised to 36° C. to fully react for 5.2 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0135] Step S4, dissolving the 4.3 mmol sulfonated polyethylene glycol in 238 mL dichloromethane, adding 4.4 mmol triethylenetetramine, stirring at 280 rpm under nitrogen protection with a ventilation rate of 6.3 mL / min, reacting at 40° C. for 5.0 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0136] Step S5, dissolving 2.0 mmol of terminal amide polylactic acid and 6.0 mmol of multi-point cross-linked sulfonated polyethylene glycol in 200 mL of dichloromethane, adding 0.44 g of stannous octoate, fully reacting at 122° C. for 4.8 hours, performing ring-opening polymerization, and adding 1.2 g of 2,6-di-tert-butyl-4-methylphenol and 1.3 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0137] Example 7

[0138] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0139] Step S1, dissolving 7.5 mmol of polylactic acid in 220 mL of dichloromethane, stirring at 370 rpm for 41 min to fully dissolve the polylactic acid, adding 4.3 mL of ethylenediamine monohydrate and 0.39 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 6.8 mL / min, then heating to 51° C. to fully react for 4.6 h. After the reaction is completed, the cooled polymer solution is added to a 4.5° C. cold ethanol solution, and the solution is stirred at 250 rpm for 23 min to ensure that the polymer in the solution is evenly dispersed and precipitated. After standing for 15 min, the precipitate is collected and washed with cold ethanol, and the residual ethanol is removed using a rotary evaporator to obtain amino polylactic acid;

[0140] Step S2, dissolving the 2.9 mmol of the amino polylactic acid in 210 mL of dichloromethane, adding 3.0 mmol of N-hydroxysuccinimide and 1.3 g of N,N'-dicyclohexylcarbodiimide, heating to 42° C. under nitrogen protection at a ventilation rate of 6.8 mL / min, and fully reacting at a speed of 370 rpm for 3.6 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0141] Step S3, dissolving 7.7 mmol polyethylene glycol in 230 mL dry dichloromethane, stirring at 430 rpm for 27 min to fully dissolve the polyethylene glycol, adding 8.9 mmol sulfonyl chloride and 2.6 mL triethylamine under nitrogen protection at a ventilation rate of 6.8 mL / min, and maintaining the reaction temperature at 3.0° C. After the addition is completed, the temperature is raised to 33° C. to fully react for 4.2 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0142] Step S4, dissolving the 3.4 mmol sulfonated polyethylene glycol in 225 mL dichloromethane, adding 4.5 mmol triethylenetetramine, stirring at 290 rpm under nitrogen protection with a ventilation rate of 6.8 mL / min, reacting at 41° C. for 5.2 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0143] Step S5, dissolving 3.0 mmol of terminal amide polylactic acid and 9.0 mmol of multi-point cross-linked sulfonated polyethylene glycol in 220 mL of dichloromethane, adding 0.37 g of stannous octoate, fully reacting at 121° C. for 5.8 hours, performing ring-opening polymerization, and adding 1.5 g of 2,6-di-tert-butyl-4-methylphenol and 1.8 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0144] Example 8

[0145] This embodiment provides a method for preparing a low viscosity thickener for water-based wood coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0146] Step S1, dissolving 5.9 mmol of polylactic acid in 210 mL of dichloromethane, stirring at 320 rpm for 48 min to fully dissolve the polylactic acid, adding 4.1 mL of ethylenediamine monohydrate and 0.35 g of isophorone diisocyanate under nitrogen protection at a ventilation rate of 5.6 mL / min, then heating to 55° C. to fully react for 5.3 h. After the reaction is completed, the cooled polymer solution is added to a 6.0° C. cold ethanol solution, and the solution is stirred at 240 rpm for 26 min to ensure that the polymer in the solution is evenly dispersed and precipitated. After standing for 17 min, the precipitate is collected and washed with cold ethanol, and the residual ethanol is removed using a rotary evaporator to obtain amino polylactic acid;

[0147] Step S2, dissolving the 3.7 mmol of the amino polylactic acid in 230 mL of dichloromethane, adding 3.8 mmol of N-hydroxysuccinimide and 1.6 g of N,N'-dicyclohexylcarbodiimide, heating to 44°C under nitrogen protection at a ventilation rate of 5.6 mL / min, and fully reacting at a speed of 430 rpm for 4.2 hours. After the reaction is completed, the precipitated product is washed with cold ethanol, and the residual ethanol is removed by rotary evaporation to obtain terminal amide polylactic acid;

[0148] Step S3, dissolving 7.5 mmol polyethylene glycol in 220 mL dry dichloromethane, stirring at 470 rpm for 24 min to fully dissolve the polyethylene glycol, adding 8.6 mmol sulfonyl chloride and 2.5 mL triethylamine under nitrogen protection at a ventilation rate of 5.6 mL / min, and maintaining the reaction temperature at 4.0° C. After the addition is completed, the temperature is raised to 37° C. to fully react for 5.6 h, and dichloromethane is removed by rotary evaporation, and the sulfonated polyethylene glycol is precipitated and purified in cold ethanol;

[0149] Step S4, dissolving the 3.7 mmol sulfonated polyethylene glycol in 215 mL dichloromethane, adding 3.8 mmol triethylenetetramine, stirring at 330 rpm under nitrogen protection with a ventilation rate of 5.6 mL / min, reacting at 40° C. for 5.6 h, removing dichloromethane by rotary evaporation, precipitating with cold ethanol and washing for multiple times to obtain multi-point cross-linked sulfonated polyethylene glycol;

[0150] Step S5, dissolving 2.8 mmol of terminal amide polylactic acid and 8.4 mmol of multi-point cross-linked sulfonated polyethylene glycol in 230 mL of dichloromethane, adding 0.42 g of stannous octoate, fully reacting at 116° C. for 5.7 h, performing ring-opening polymerization, and adding 1.3 g of 2,6-di-tert-butyl-4-methylphenol and 1.5 g of 2-(2'-hydroxy-5'-octylphenyl)benzotriazole. After the reaction is completed, removing dichloromethane by rotary evaporation, precipitating and washing with cold ethanol, and obtaining a low-viscosity thickener for water-based wood coatings.

[0151] Comparative Example 1

[0152] This embodiment provides a low viscosity thickener for waterborne wood coatings, which differs from Example 1 in that the amount of the multi-point cross-linked sulfonated polyethylene glycol is adjusted to 7.3 mmol. Compared with Example 1, the amount of the multi-point cross-linked sulfonated polyethylene glycol in this embodiment is increased by 1 mmol, and the increased 1 mmol is deducted from the equal proportion of 2,6-di-tert-butyl-4-methylphenol and 2-(2'-hydroxy-5'-octylphenyl)benzotriazole, so that the mass ratio between the other components except the multi-point cross-linked sulfonated polyethylene glycol remains unchanged, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0153] Comparative Example 2

[0154] This embodiment provides a low viscosity thickener for waterborne wood coatings, which differs from Example 1 in that the amount of multi-point cross-linked sulfonated polyethylene glycol is adjusted to 5.3 mmol. Compared with Example 1, the mass of the multi-point cross-linked sulfonated polyethylene glycol in this embodiment is reduced by 1 mmol, and the reduced 1 mmol is added in equal proportion to the mass of 2,6-di-tert-butyl-4-methylphenol and 2-(2'-hydroxy-5'-octylphenyl)benzotriazole, so that the mass ratio between the other components except the multi-point cross-linked sulfonated polyethylene glycol remains unchanged, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0155] Comparative Example 3

[0156] This embodiment provides a low viscosity thickener for water-based wood coatings, which differs from Example 1 in that the amount of triethylenetetramine is adjusted to 5.3 mmol. Compared with Example 1, the amount of triethylenetetramine in this embodiment is increased by 2.5 mmol. Except for the mass ratio between other components of triethylenetetramine, the other process parameters and operating steps are exactly the same as those in Example 1.

[0157] Comparative Example 4

[0158] This embodiment provides a low viscosity thickener for water-based wood coatings, which differs from Example 1 in that the amount of triethylenetetramine is adjusted to 0.3 mmol. Compared with Example 1, the amount of triethylenetetramine in this embodiment is reduced by 2.5 mmol. Except for the mass ratio between other components of triethylenetetramine, the other process parameters and operating steps are exactly the same as those in Example 1.

[0159] The anti-sagging property of the low-viscosity thickener coating for water-based wood coatings prepared by the present invention is tested according to the national standard GB / T 9264-2012; the viscosity of the low-viscosity thickener coating for water-based wood coatings prepared by the present invention is tested according to the national standard GB / T 9269-2009; the leveling test is carried out under constant temperature and humidity conditions, and a paint film is prepared on a tinplate with a paint brush. When brushing, the paint is quickly applied vertically first and then horizontally, and the brushing time does not exceed 2 to 3 minutes. Then, a line is brushed vertically from one side to the other in the middle of the sample (with brush marks but without exposing the bottom), and the timing starts from the moment the brush leaves the sample, and the time required for the brush mark to disappear and a smooth paint film surface to be formed is measured.

[0160] Table 1 Test results of low viscosity thickeners for waterborne wood coatings in Examples 1-8 and Comparative Examples 1-4

[0161] .

[0162] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the anti-sagging property and coating viscosity of Comparative Example 1 are higher than those of Example 1, and the leveling effect is lower than that of Example 1; the anti-sagging property and coating viscosity of Comparative Example 2 are lower than those of Example 1, and the leveling effect is higher than that of Example 1. This is because the mass fraction of multi-point cross-linked sulfonated polyethylene glycol in Comparative Example 1 is relatively high, and the sulfonic acid groups in the multi-point cross-linked sulfonated polyethylene glycol form multiple cross-linking points with multiple amine sites. Excessive addition of multi-point cross-linked sulfonated polyethylene glycol will lead to excessive cross-linking density, increased viscosity of the coating, and poor fluidity of the coating; while in Comparative Example 2, the mass fraction of multi-point cross-linked sulfonated polyethylene glycol is relatively low, the cross-linking points are reduced, the three-dimensional network structure of the thickener is not stable enough, the thickening effect is weakened, the viscosity of the coating is insufficient, and sagging may occur.

[0163] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the anti-sagging property and coating viscosity of Comparative Example 3 are higher than those of Example 1, and the leveling effect is lower than that of Example 1; the anti-sagging property and coating viscosity of Comparative Example 4 are lower than those of Example 1, and the leveling effect is higher than that of Example 1. This is because the polyamine groups of the excess triethylenetetramine in Comparative Example 3 undergo cross-linking reactions with the functional groups in the sulfonated polyethylene glycol and the amidated polylactic acid. If too much triethylenetetramine is added, the cross-linking density in the system will be too high, forming an over-cross-linked three-dimensional network structure, resulting in reduced leveling and excessive coating viscosity; in Comparative Example 4, too little triethylenetetramine is added, the cross-linking points in the system will be reduced, and a sufficient three-dimensional network structure cannot be formed, resulting in a significant weakening of the thickening effect and poor anti-sagging performance.

[0164] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a low viscosity thickener for water-based wood coatings, characterized in that: The preparation method comprises: Step S1, dissolving polylactic acid in a reaction solvent, adding an amination reagent and a first catalyst under the protection of an inert gas, then heating to a first temperature for sufficient reaction, after the reaction is completed, adding the cooled polymer solution to a cold ethanol solution, collecting the precipitate after standing, and washing it with cold ethanol to obtain an amination polylactic acid; Step S2, dissolving the amino polylactic acid in a reaction solvent, adding an amidation agent and a second catalyst, heating to a second temperature under the protection of an inert gas for sufficient reaction, and washing the precipitated product with cold ethanol after the reaction to obtain terminal amide polylactic acid; Step S3, dissolving polyethylene glycol in a dry reaction solvent, adding a sulfonating agent and a third catalyst under the protection of an inert gas, and maintaining the reaction temperature at the third temperature, heating to a fourth temperature after the addition is completed to fully react, and precipitating and purifying in cold ethanol to obtain sulfonated polyethylene glycol; Step S4, dissolving the sulfonated polyethylene glycol in a reaction solvent, adding a cross-linking agent, fully reacting at a fifth temperature under the protection of an inert gas, precipitating with cold ethanol and washing for multiple times to obtain a multi-point cross-linked sulfonated polyethylene glycol; Step S5, dissolving the terminal amide polylactic acid and the multi-point cross-linked sulfonated polyethylene glycol in a reaction solvent, adding a fourth catalyst, fully reacting at a sixth temperature, performing ring-opening polymerization, adding an antioxidant and an ultraviolet absorber, and after the reaction is completed, using cold ethanol for precipitation and washing to obtain a low-viscosity thickener for water-based wood coatings; In step S4, the cross-linking agent is triethylenetetramine, and the amount of the substance is 2.1-5.1 mmol; In step S5, the amount of the terminal amide polylactic acid is 2-4 mmol, and the amount ratio of the multi-point cross-linked sulfonated polyethylene glycol to the terminal amide polylactic acid is 3:

1.

2. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S1, The amount of the polylactic acid is 5-10 mmol; The reaction solvent is dichloromethane, with a volume of 200-250 mL; The inert gas is nitrogen, and the ventilation rate is 5-7 mL / min; The amination reagent is ethylenediamine monohydrate, and the added volume is 3-5 mL.

3. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S1, The first catalyst is isophorone diisocyanate, with a mass of 0.2-0.5 g; The first temperature is 40-60°C, and the reaction time is 4-6h; The temperature of the cold ethanol is 0-8°C; The standing time is 10-20 minutes.

4. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S2, The amount of the amino polylactic acid is 2-5 mmol; The reaction solvent is dichloromethane, the volume is 200-250mL; The amidation reagent is N-hydroxysuccinimide, and the amount of the substance is 2-5 mmol; The second catalyst is N,N'-dicyclohexylcarbodiimide, with a mass of 1-2 g.

5. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S2, The inert gas is nitrogen, and the ventilation rate is 5-7 mL / min; The second temperature is 40-50°C; The reaction time at the second temperature is 3-5h.

6. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S3, The amount of the polyethylene glycol is 5-10 mmol; The reaction solvent is dichloromethane, with a volume of 200-250 mL; The inert gas is nitrogen, and the ventilation rate is 5-7 mL / min; The sulfonating agent is sulfonyl chloride, and the amount of the substance is 6-11 mmol.

7. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S3, The third catalyst is triethylamine, with a volume of 2-3 mL; The third temperature is 0-5°C; The fourth temperature is 30-40°C, and the reaction time is 4-6h.

8. The method for preparing a low viscosity thickener for waterborne wood coatings according to claim 1, characterized in that: In step S4, The amount of the sulfonated polyethylene glycol is 2-5 mmol; The reaction solvent is dichloromethane, with a volume of 200-250 mL; The inert gas is nitrogen, and the ventilation rate is 5-7 mL / min; The fifth temperature is 35-45°C, and the reaction time is 4-6h.

9. The method for preparing a low viscosity thickener for water-based wood coatings according to claim 1, characterized in that: In step S5, The reaction solvent is dichloromethane, with a volume of 200-250 mL; The fourth catalyst is stannous octoate, with a mass of 0.2-0.5g; The sixth temperature is 110-130°C, and the reaction time is 4-6h; The antioxidant is 2,6-di-tert-butyl-4-methylphenol, with a mass of 1-2g; The ultraviolet absorber is 2-(2'-hydroxy-5'-octylphenyl)benzotriazole, with a mass of 1-2 g.

10. A low viscosity thickener for waterborne wood coatings prepared by the preparation method according to any one of claims 1 to 9.